CRYPTOCURRENCY IN INDONESIAN FINANCIAL STATEMENT: A LITERATURE STUDY - Fatturrozi, Dwiyan (Jurnal KIAFE, 2022)
Cryptocurrencies require regulations that include determining the methods of valuation and reporting of cryptocurrencies in the company's financial statements. The purpose of this research is to determine the means of accounting records and classification of cryptocurrencies on financial statements whether cryptocurrencies are considered as based on the relevant accounting standards in Indonesia. This research is a literature study. Secondary data source used by the author is data related to several literatures related to accounting standards in Indonesia. The findings of this study, company ownership of cryptocurrency can be classified as an asset under PSAK. The most relevant type of asset classification for Cryptocurrencies is inventory or intangible assets.